MATH SOLVE

2 months ago

Q:
# 1.) For the following system, use the second equation to make a substitution for x in the first equation. 3x + 2y = 7x - y + 3 = 0 What is the resulting equation? a. 3x - y - 3 + 2y = 7b. 3(y - 3) + 2y = 7c. 3y - 3 + 2y = 72.) Which of the following would not be the result of a substitution in the following system?2x + y = 7y - x = 1a. 7 - 2x - x = 1b. 2x + x + 1 = 7c. 2(y + 1) + y = 73.)Solve the following system of equations by the substitution method. 8x = 2y + 53x = y + 7What is the solution set?a. {(-41/2, -9/2)}b. {(-9/2, -41/2)}c. β

Accepted Solution

A:

1.)-b. 2)-.b.3)-b I am sure